Research Article LEAVES EXTRACT-BASED BIOGENIC SYNTHESIS OF CUPRIC OXIDE NANOPARTICLES, CHARACTERIZATIONS, AND ANTIMICROBIAL ACTIVITY - CHANDRA JOSHI, NAVEEN; YASHWANI PRAKASH (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: Tulsi (Ocimum tenuiflorum) leaves extract-based synthesis of cupric oxide nanoparticles (CuONPs), characterizations, and antimicrobial activity. Methods: The small cut leaves were washed with double distilled water and boiled for 30 min. After filtration, the extract was treated with 0.2 M copper acetate solution and the initial color change of this solution indicated formation of copper nanoparticles. This solution was stirred for a specific time, heated and treated with 0.1 M NaOH solution. The formation of CuONPs was confirmed by the development of brownish-black precipitates. Then, CuONPs have been tested for their antibacterial effects by applying well diffusion method against Escherichia coli, Streptococcus mutans, Proteus vulgaris, and Staphylococcus aureus. Results: The biologically synthesized CuONPs have been well characterized by using ultraviolet-visible, Fourier-transform infrared, X-ray powder diffraction, and field-emission scanning electron microscopy techniques and all these analytical methods indicated a successful and efficient formation of CuONPs. After the incubation period, significant zones of inhibition were observed for E. coli, S. mutans, P. vulgaris, and S. aureus. Conclusions: The method was found highly efficient, eco-friendly, and low cost for the synthesis of biologically important CuONPs. The CuONPs have been found an excellent antibacterial agent.